1993
DOI: 10.1099/00207713-43-4-694
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for Rejection of Agrobacterium tumefaciens and Revised Descriptions for the Genus Agrobacterium and for Agrobacterium radiobacter and Agrobacterium rhizogenes

Abstract: The 16s rRNA sequences of seven representative Agrobacterium strains, eight representative Rhizobium strains, and the type strains of Azorhizobium caulinodans and Bradyrhizobium japonicum were determined. These strains included the type strains of Agrobacterium tumefaciens, Agrobacterium rhizogenes, Agrobacterium radiobacter, Agrobacterium vitis, Agrobacterium rubi, Rhizobium fredii, Rhizobium galegae, Rhizobium huukuii, Rhizobium leguminosarum, Rhizobium loti, Rhizobium meliloti, and Rhizobium tropici. A phyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
154
1
3

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(162 citation statements)
references
References 38 publications
4
154
1
3
Order By: Relevance
“…The precise taxonomic position of the R. galegae strains is not yet clear. There is some evidence of their phylogenetic linkage to R. loti strains (36), but other authors showed them to be divergent from R. loti and demonstrated that they were more closely related to Agrobacten'urn species (23,31). The results of mobilization of symbiotic genes from R. galegae into Agrobactenum strains would seem to support the second finding (18).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The precise taxonomic position of the R. galegae strains is not yet clear. There is some evidence of their phylogenetic linkage to R. loti strains (36), but other authors showed them to be divergent from R. loti and demonstrated that they were more closely related to Agrobacten'urn species (23,31). The results of mobilization of symbiotic genes from R. galegae into Agrobactenum strains would seem to support the second finding (18).…”
Section: Discussionsupporting
confidence: 69%
“…biovar 2 or R. Zegurninosarurn than it is to Agrobacten'urn sp. biovar 1 (14,16,23,31). Nevertheless, the symbiotic plasmid of CIAT 899 can be expressed in an A. tumefaciens C58 genetic background (15), and this fact suggests a degree of phenotypic relatedness between these two strains.…”
Section: Discussionmentioning
confidence: 99%
“…These groups include exceptionally slowly growing soybean rhizobia (personal communication) and groups of fast-growing rhizobia isolated from tropical regions Extensive studies on the phylogenetic relationships of rootand stem-nodulating bacteria in which workers have used 16s rRNA (ribosomal DNA) sequencing or rRNA-DNA hybridization have revealed that all previously described rhizobia belong to the alpha subclass of the Proteobacteria (7, 12, 13, 19, 23, [25][26][27][28][29][30] and that both the genus Rhizobium and the genus Bradyrhizobiurn are much more closely related to their corresponding nonsymbiotic relatives than to each other. Several distinct lineages have been identified in the genus Rhizobium, including the R. leguminosarum-R. tropici lineage, the R. meliloti-R. fredii lineage, the R. huakuii-R. loti lineage, and the R. galegae lineage (19,27). Considering the fact that Agrobacterium, Phyllobacterium, Mycoplana, Brucella, and Ochrobacterium species are embedded in Rhizobium lineages (19,(25)(26)(27), these Rhizobium lineages might represent separate genera (19,(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…Several distinct lineages have been identified in the genus Rhizobium, including the R. leguminosarum-R. tropici lineage, the R. meliloti-R. fredii lineage, the R. huakuii-R. loti lineage, and the R. galegae lineage (19,27). Considering the fact that Agrobacterium, Phyllobacterium, Mycoplana, Brucella, and Ochrobacterium species are embedded in Rhizobium lineages (19,(25)(26)(27), these Rhizobium lineages might represent separate genera (19,(25)(26)(27)(28)(29)(30). The genus Bradyrhizobium constitutes a separate lineage and is closely related to Rhodopseudomonas palustrih, Blastobacter denitrifcans, and the genera Ajipia, and Nitrobacter (25,26).…”
mentioning
confidence: 99%
“…have been divided into three distinct systematic units called biovar 1, biovar 2 and biovar 3 based on physiological characteristics. Later classification using rDNA sequences confirmed the biovar grouping as proposed by Sawada et al (1993), although the conventional pathovar grouping is still in common use.…”
Section: Introductionmentioning
confidence: 96%